STUDIES ON THE PROGRESSION FACTORS WITH REFERENCE TO FOOD UTILIZATION AND ALLOMETRY OF LASIOCAMPID CATERPILLARS (LEPIDOPTERA) - KRISHNARAO, P.; GOEL, S. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Thirty two variables of head and body appendages are verified for geometrical progression in addition to the width of head capsule during the larval period of Trabala vishnu Lef The growth ratios of linear measurements show a progressive decrease between the instars as being 1.63, 1.52, 42, 1.35 and 1.26 against the mean progression factor 1 44 Considering food consumption and utilization values, the decrease in weight specific consumption, assimilation and tissue growth with increase in age and body weight are assessed as a possible reason for the decrease in growth ratios of the head and body appendages. Food and temperature made no effect on the number of instars, nevertheless, responsible for variation in the larval duration The growth ratios both for body weight and linear measurements exceed the value required under Przibram's theory, while the length of body as a whole and its parts have shown perfect allometric growth.